Value and Use of Pediatric Postmortem Magnetic Resonance Imaging. - Beam, Asher Street; Stephens, Chelsea; Moore, Kristi; Taylor, Charlotte; Bolton, Haley; Cain, Richard; Miller, Shae; Wright, Victoria (Radiologic Technology)
Background The gold standard for postmortem investigations of fetal and pediatric deaths involving neurological pathologies is a traditional autopsy; however, acquiring all diagnostic information from an autopsy alone can be challenging. In addition, there are substantial obstacles to performing traditional autopsies on the pediatric population such as parental opinion, religious beliefs, and cultural backgrounds. Postmortem computed tomography, sonography, and magnetic resonance (MR) imaging are less invasive alternative approaches for investigating central nervous system-- related deaths. Although restrictions in functionality of postmortem MR imaging exist, it is the preferred approach to investigate cause of death. Discussion Postmortem MR imaging helps diagnose brain, heart, and musculoskeletal abnormalities, providing information not obtainable through neuropathology due to tissue deterioration. The less invasive approach of postmortem MR imaging, paired with its capability to visualize soft tissue and detect minute alterations, makes this modality a highly valued method for analyzing neurological pathologies. Although traditional autopsy might take weeks to obtain a diagnosis, postmortem MR imaging lessens the duration to hours. Conclusion Postmortem imaging has the potential to ease the drawbacks of autopsy such as parental acceptance and nervous tissue autolysis. It also can help determine the cause and time of death. Although postmortem MR imaging has disadvantages, its benefits compared with conventional autopsy warrant its use. With the appropriate research and educational offerings, this modality can overcome the limitations of traditional autopsy and become the new gold standard of postmortem investigations of pediatric cases.